Evaluating Conditions for Moored Fish Aggregating Device Fisheries Development in the Caribbean and Bermuda - Wilson, Margaret W.; Lawson, Julia M.; Rivera-Hechem, María Ignacia; Villaseñor-Derbez, Juan Carlos; Gaines, Steven D. (Frontiers in Marine Science, 2022)
Moored fish aggregating devices (MFADs) are promoted in small-scale fisheries around the world as tools to increase fisher incomes, enhance food security, and ease pressure on degraded inshore fisheries. Despite their growing popularity, the biophysical and socioeconomic contexts in which MFAD fisheries are implemented - and the implications of these contexts for MFAD fishery success - remain poorly understood. Here we develop a framework identifying and evaluating factors likely to influence MFAD fishery outcomes and apply it across states in the insular Caribbean region. We highlight the heterogeneity in MFAD regulatory strength, catch marketability, social need, and costs among states and discuss best approaches for optimizing MFAD benefits across different socioeconomic scenarios.